Metaphorical Symbols Used in Linkin Park’s Song Lyrics and its Contribution to Teaching Poetry - Novita Anggraini; Listyaning Sumardiyani; Faiza Hawa (Universitas PGRI Semarang, 2017)
The objectives of this study are: 1) to find out the meaning of metaphorical symbols in Linkin Park’s song lyrics; 2) to find out the contribution of Linkin Park’s song lyrics to teaching poetry. In this study, the writer applies the descriptive qualitative approach in this study to analyze implicit meaning of metaphorical symbols used in Linkin Park’s song lyrics. Besides that, the writer wants to describe its contribution to teaching poetry. The finding show that the writer found 38 metaphorical symbols in the five Linkin Park’s song lyric. It consists of 4 symbols in the Numb, 14 symbols in Hands Held High, 5 symbols in What I’ve done, 5 symbols in New Divide, 10 symbols in Final Masquerade. Through using those song lyrics, the students can learn the figurative languages which can be found in those song lyrics, especially metaphorical symbols. The students can understand the meaning of the metaphorical symbols which can enrich their vocabulary through learn the examples of implicit meaning analysis in this study. So they are able to choose and combine the appropriate dictions. Finally, they will be able to create a good poetry which has deep and beautiful meaning. The writer suggests that the teachers should use an appropriate and interesting learning source in teaching writing and appreciating poetry. Song lyrics in Linkin Park consist of a lot of words, phrases, and sentences with the figurative language, especially metaphorical symbols which has implicit and deep meaning. Through delivering those songs lyrics, the students will get the inspiration and motivation in writing and appreciating poetry.